Impact of Mézières Rehabilitative Method in Patients with Parkinson's Disease: A Randomized Controlled Trial. (3rd December 2017) - Paolucci, Teresa; Zangrando, Federico; Piccinini, Giulia; Deidda, Laura; Basile, Rossella; Bruno, Enrico; Buzi, Emigen; Mannocci, Alice; Tirinelli, Franca; Haggiag, Shalom; Lispi, Ludovico; Villani, Ciro; et al.
Abstract : The aim of this study was to assess the efficacy of Mézières method in improving trunk flexibility of the back muscles and balance in patients with Parkinson's disease (PD). Materials and Methods . Thirty-six patients were randomized into 2 groups: the Mézières treatment group and the control group (home exercise group). The primary outcome was the improvement in balance per the Berg Balance Scale (BBS) and the trunk flexibility of the back for the anterior flexion trunk test. Also, we evaluated pain, gait balance for the Functional Gait Assessment (FGA), disease-related disability for the Modified Parkinson's Activity Scale and the Unified Parkinson's Disease Rating Scale (UPDRS), the quality of life, and the functional exercise capacity. All the measures were evaluated at baseline (T 0 ), at the end of the rehabilitative program (T 1 ), and at the 12-week follow-up (T 2 ). Results . In the Mézières group, the BBS (p < . 001 ) and trunk flexion test (p < . 001 ) improved significantly atT 1 and remained the same atT 2 . Between groups, significant changes were reported in FGA (p = . 027 ) and UPDRS Total (p = . 007 ) atT 1 and in FGA (p = . 03 ) atT 2 . Conclusion . The Mézières approach is efficacious in improving the flexibility of the trunk and balance in PD patients.